Water demands of bean crop in Northwest of Sao Paulo - Farinassi, Larissa Godarelli [UNESP]; Tangerino Hernandez, Fernando Braz [UNESP]; Bispo, Regiane de Carvalho [UNESP] (Univ Federal Reconcavo Bahia, 2020)
Common beans (Phaseolus vulgaris L.) is a crop of great socioeconomic importance for Brazil, being the second largest producer and main world consumer. This work aimed to evaluate the inuence of reference evapotranspiration (ETo) on the accuracy of estimates of water demand for common beans at different sowing times and municipalities in the Northwest region of Sao Paulo. The study was carried out under conditions irrigated by a central pivot with seven seasons of winter bean sowing in the municipalities of Rubineia and Pereira Barreto. In each sowing, he used ETo from agrometeorological stations in Ilha Solteira, Marinopolis and Bonanca and also the historical base represented by the Reference E Evapotranspiration Zones (ETo Zone). It was verified that the irrigation management in the sowing carried out in Rubineia can be done using the Ilha Solteira or Marinopolis Station, with no difference between the water demand throughout the cycle, however sowing carried out in Pereira Barreto should have the Bonanca Station as preference for the estimate of ETo, followed by Eto Zone 2, however, if there are irrigators on the banks of the Tiete and Parana rivers, it is recommended to be attentive to the direction of the winds, because in some seasons the winds can transport air masses from the river to the continent.
Keywords: Phaseolus vulgaris L.; evapotranspiration; wind; weather stations